2020
DOI: 10.3390/su122310213
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science as Part of the Primary School Curriculum: A Case Study of a Technical Day on the Topic of Noise and Health

Abstract: In this paper, we summarise lessons learned conducting citizen science (CS) activities within the CitieS-Health H2020 project on the topic of noise exposure and health at a primary school in Ljubljana, Slovenia. Activities were organised in the form of a School Tech-Day Event (STDE) as part of the school’s curriculum involving second-grade pupils, ages 7–8. The STDE was aligned with the project’s methodological framework, which is based on co-creation and co-design principles. To this end, the pupils initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Previous citizen science studies also showed the participants' abilities to recognise environmental-level problems, but they had little influence on changes in the participants' behaviour or the socioecological system [20,40]. The participatory action research found that an increase in scientific knowledge increases public awareness and contributes to scientific literacy [41]. Participation in citizen science could contribute to the SDGs by defining local targets, monitoring the progress, and having the potential to implement action [3,39,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous citizen science studies also showed the participants' abilities to recognise environmental-level problems, but they had little influence on changes in the participants' behaviour or the socioecological system [20,40]. The participatory action research found that an increase in scientific knowledge increases public awareness and contributes to scientific literacy [41]. Participation in citizen science could contribute to the SDGs by defining local targets, monitoring the progress, and having the potential to implement action [3,39,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature provides examples of the implementation of an interactive learning model in educational practice. For example, (Kocman et al, 2020) describes the experience and results of the implementation of the method of joint design of scientific research of natural phenomena in the second grade. The relationship between learning style and interactive methods and student achievement is noted (Tomuletiu et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The benefits of citizen science can also relate to formal education, through the implementation of classroom practices in school curricula (Kocman et al, 2020;Queiruga-Dios et al, 2020;Vitone et al, 2016). Thanks to this, students can participate from an early age in projects that improve their attitudes towards science and help to break stereotypes about scientists, increasing their interest in science and technology (Benavent et al, 2020;Queiruga-Dios et al, 2020).…”
Section: ■ Citizen Science and Scientific Literacymentioning
confidence: 99%